Tactics of Treatment for Idiopathic Thrombocytopenic Purpura in Pregnant Women - Ergashev Ulugbek Yusufjanovich; Soxibova Gulnoza Komilovna; Atakhodjaeva Fotima Abduraimovna (Genius Journals, 2023)
The article shows the results of 12 pregnant women with a complication of idiopathic thrombocytopenic purpura in the form of hemorrhagic syndrome. Their clinic, diagnosis, conservative and surgical treatment.Traditional and inhalation injection of glucocorticoid hormones, as well as intravenous injection of immunoglobulin in 75% of patients had positive effect and remission was obtained on days 3-4. If the conservative treatment was ineffective, surgeries were performed splenectomy (SE), and uterine bleeding stopped on 2-3 days and platelets increased to 210 thousand. During pregnancy, patients with idiopathic thrombocytopenicpurpura (ITP), complicated by hemorrhagic syndrome, conservative and surgical treatment in 100% of cases performed a positive effect
Keywords: immune thrombocytopenia; pregnancy; delivery